Pola Komunikasi Nonverbal Guru Busana Dalam Memberikan Instruksi Praktik Kepada Peserta Didik Tunarungu SMKN 10 Medan - Alya Habibah; Akhyar Anshori (Universitas Muhammadiyah Sumatera Utara, 2026)
Nonverbal communication plays an important role in the learning process, particularly for deaf students who rely heavily on visual aspects in receiving information. In practical learning at vocational high schools (SMK), nonverbal communication is used by teachers as the primary means of delivering instructions so that students can understand the procedural steps accurately. This study aims to analyze the pattern of nonverbal communication used by fashion teachers in providing practical instructions to deaf students at SMKN 10 Medan. This study employs a qualitative method with a descriptive approach. Data collection techniques were carried out through interviews, observations, and documentation involving fashion teachers as the main informants. The data were then analyzed through data reduction, data presentation, and conclusion drawing. The results of the study indicate that nonverbal communication is the main strategy in delivering practical instructions, including the use of hand gestures, clear lip movements, facial expressions, and direct demonstrations. In addition, the use of visual instructions such as written explanations and direct examples helps students understand the procedural steps systematically. Teachers also apply flexible and adaptive communication through repeated explanations and the use of peer assistance.